HYGIENIC ANALYSIS OF DISEASES OBSERVED DURING CLIMAX PERIOD IN WOMEN - Saidova G. T.; Sayfullayeva S. G. (Modern American Journals, 2025)
Climax is not a disease, but a completely normal physiological period observed in the life of any woman after the age of 45. At this age, the ovaries in a woman's body, which are responsible not only for bearing children, but also for a woman's appearance, gradually begin to stop functioning. Our research confirms the results of previously published work that women's incidence rates increase as they age.
Keywords: Climacteric period, climacteric syndrome (CS), indicators of morbidity, age-related changes.